Inheritance of Pedicel Characters and Their Association to Fruit Characters in Capsicum annuum L. - Ridwan Setiamihardja (Zuriat, 1990)
Fruit detachment force (FDF) has shown highly correlated to the pedicel size of Capsicum annuum L. The inheritance of pedicel size (length and diameter) and their correlation to the fruit size (length and diameter) were evaluated from the cross 'Serrano' x 'KRG'. Pedicel length and diameter apparently were inherited as quantitative characters, mainly in additive manner, with very low heritability estimates, 4.4% and 8.5%, respectively. Correlation coefficient between fruit diameter and pedicel diameter was positive and significant at 1% level. There was an indication of linkage or pleiotropy between fruit diameter and pedicel diameter.